Effects of amine-functionalization on mixed matrix membranes encompassing of T-type zeolite and 6FDA-based polyimide for separation of CO2 from CH4 - Jusoh, N. (Universiti Malaysia Pahang, 2018)
Mixed matrix membranes (MMMs) comprising of unfunctionalized and amine-functionalized T-type zeolite and 6FDA-based polyimide matrix were formulated. The physicochemical properties of the membranes were examined by FESEM, EDX, TGA and DSC. FESEM images showed that the enhancement of polymer-zeolite adhesion in MMM embedded with amine-functionalized T-type zeolite is trivial in comparison with MMM loaded with unfunctionalized T-type zeolite. From permeation test, permeability of CO2 of 858 Barrer and selectivity of CO2/CH4 of 22.5 was obtained using MMM incorporated with amine-functionalized T-type zeolite, whereas MMM incorporated with unfunctionalized T-type zeolite displayed permeability of CO2 of 844 Barrer and selectivity of CO2/CH4 of 19.1. Thus, selection of another suitable amine-functionalization group might be required in later works to further improve MMM performance in capturing CO2 from CH4. Â© Universiti Malaysia Pahang, Malaysia.